2020
DOI: 10.1159/000507510
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Tobacco Smoking/Electronic Smoking and Albuminuria/Vascular Stiffness in Young People without Cardiovascular Diseases

Abstract: Introduction/Objective: Tobacco smoking is a well-known risk factor for cardiovascular and renal diseases. In recent years, alternative types of smoking, including vaping, have been becoming popular. The contribution of vape to vascular and renal injury is not known. We studied the relation between smoking of traditional/electronic cigarettes and arterial stiffness and albuminuria, which is also a vascular dysfunction marker. Methods: We examined 270 young volunteers without significant clinical cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
(68 reference statements)
1
17
0
1
Order By: Relevance
“…Numerous studies found a link between tobacco smoking and severe diseases such as cancers, cardiovascular, respiratory diseases, and stroke [ 1 , 31 , 32 ]. However, the effect of tobacco and, more specifically, WPS on the embryos is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies found a link between tobacco smoking and severe diseases such as cancers, cardiovascular, respiratory diseases, and stroke [ 1 , 31 , 32 ]. However, the effect of tobacco and, more specifically, WPS on the embryos is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Smoking Cessation plaque (p < 0:0001), microvascular endothelial dysfunction, and reduced endothelial nitric oxide (eNOS) levels (2.6%; p = 0:018) that related with endothelial dysfunction [15,[17][18][19]. One study did not compare effects of using electronic cigarettes with nonusers but observed that the markers of platelet activation (29%; p = 0:04), oxidative stress (23%; p = 0:02), and endothelial dysfunction (16%; p = 0:02) of electronic cigarette users were lower than conventional cigarette users [16].…”
Section: Resultsmentioning
confidence: 99%
“…The difference in generated products of e-liquid and tobacco leaf is evidence for smokers to switch from conventional cigarettes to electronic cigarettes [11-13, 16, 19, 20]. However, long-term exposure to the mentioned eliquid heating byproducts, though in little amounts, still explains the health chronic effects that are supported by the rest of the studies [15,[17][18][19][21][22][23][24][25][26].…”
Section: Journal Of Smoking Cessationmentioning
confidence: 99%
“…Smoking-related renal injury shares pathophysiological mechanisms with diabetic nephropathy and hypertension, such as insulin resistance and increased sympathetic nervous activity [ 18 ], which is why an increase in albuminuria, proteinuria, and hyperfiltration is observed in most studies on the relationship between tobacco consumption and kidney damage (alterations similar to those pathologies) [ 19 , 20 , 21 ]. Our study confirms these findings for smokers with risk factors and also demonstrates the effect of smoking on urinary albumin/protein excretion in subjects from the general population with apparently normal kidney function, as described in a study by Halimi et al [ 22 ] conducted with 28,409 subjects.…”
Section: Discussionmentioning
confidence: 99%